Sport business in the United States : contemporary perspectives - Pitts, Brenda G.; Zhang, James J. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Sport is big business in the USA. From collegiate sport through to the professional leagues, the sport industry generates huge revenues, employs thousands of people and engages millions of fans and consumers. This book offers an evidence-based snapshot of the contemporary sport industry in the USA. Featuring new research from scholars working across every sector of sport business, the book covers key topics such as consumer behaviour, sport marketing, the development of women's sport, sport broadcasting, internships, and leadership. It adds critical depth to our understanding of the sport industry in the world's single biggest sport marketplace. Sport Business in the United States offers fascinating new perspectives for researchers, students and industry professionals. It is important reading for anybody working in sport management or sport business, whether inside the US or around the world"-- Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- Economic aspects -- United States; Sports administration -- United States